1998
DOI: 10.1086/301754
|View full text |Cite
|
Sign up to set email alerts
|

Genome Search in Celiac Disease

Abstract: Celiac disease (CD), a malabsorption disorder of the small intestine, results from ingestion of gluten. The HLA risk factors involved in CD are well known but do not explain the entire genetic susceptibility. To determine the localization of other genetic risk factors, a systematic screening of the genome has been undertaken. The typing information of 281 markers on 110 affected sib pairs and their parents was used to test linkage. Systematic linkage analysis was first performed on 39 pairs in which both sibs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
4
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 16 publications
7
123
4
3
Order By: Relevance
“…5 Apart from the HLA region, only 5q31-33, with a maximum Zlr ¼ 4.39 (P ¼ 6 Â 10 À6 ), showed genome-wide significant linkage according to standard thresholds. 6 Linkage of CD to this region was originally identified by Greco et al 7 and was also found by Naluai et al 8 and Liu et al 9 Evidence for a risk factor in 2q33 (CELIAC3), likely corresponding to the CTLA4/ICOS genes, comes from association studies mainly in Northern Europe populations. 10 The CELIAC4 locus was mapped to 19p13.1 with a maximum logarithm of odds score ¼ 4.43 in a cohort of 101 affected sib pairs belonging to 82 Dutch families.…”
Section: Introductionmentioning
confidence: 76%
“…5 Apart from the HLA region, only 5q31-33, with a maximum Zlr ¼ 4.39 (P ¼ 6 Â 10 À6 ), showed genome-wide significant linkage according to standard thresholds. 6 Linkage of CD to this region was originally identified by Greco et al 7 and was also found by Naluai et al 8 and Liu et al 9 Evidence for a risk factor in 2q33 (CELIAC3), likely corresponding to the CTLA4/ICOS genes, comes from association studies mainly in Northern Europe populations. 10 The CELIAC4 locus was mapped to 19p13.1 with a maximum logarithm of odds score ¼ 4.43 in a cohort of 101 affected sib pairs belonging to 82 Dutch families.…”
Section: Introductionmentioning
confidence: 76%
“…64 These were the second, third, fourth and fifth studies published. 62,66,68,69 The raw data consisted of genotypes from 442 families; 2025 individuals of whom 1056 are affected. The results pointed to chromosome 5q31 -33 as being the only significant locus in these families apart from HLA ( Figure 2 Figure 1 The HLA-DQ2 ab heterodimer encoded in cis and in trans.…”
Section: Epidemiology Population Geneticsmentioning
confidence: 99%
“…An alteration in the terminal portion of chromosome 5 has been identified as a risk factor for both symptomatic and silent forms of CD, whereas a change in the terminal portion of the chromosome 11 possibly differentiates the two forms. 8 Among the candidate genes, there is also a CD28/CTLA4 region on chromosome 2 that encodes receptors regulating T-lymphocyte activation. 9 Recently, multiple genetic loci have been implicated in CD pathogenesis, but their impact on the development of the disease seems to be limited as compared to that of the HLA system.…”
Section: Introductionmentioning
confidence: 99%